Acute retinal necrosis complicating chicken pox in a healthy adult: a case report and review of literature - Tajunisah, Iqbal; Reddy, Sagili Chandrasekhara (Humana Press, 2007)
We report a case of unilateral acute retinal necrosis (ARN) with marked vitritis and retinal necrosis leading to retinal breaks following chicken pox successfully treated with intravenous acyclovir followed by oral acyclovir, orbital floor triamcinolone injections to contain the inflammation, and barrier laser therapy to secure the retinal breaks with good visual outcome. This case is unusual in its severity and the novel use orbital floor triamcinolone therapy to contain ARN inflammation.